2020
DOI: 10.1557/adv.2020.220
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural and optical properties of biosynthesized Zincite (ZnO) nanoparticles (NPs) via an aqueous extract of Rosmarinus officinalis (rosemary) leaves

Abstract: Biosynthesized Zincite nanoparticles have been successfully demonstrated by a completely green process mediated aqueous extract of rosemary leaves acting as both reducing and stabilizing agents and zinc nitrate hexahydrate as the precursor. The synthesis was free of solvents and surfactants to adhere to green chemistry principles and the impartation of environmental benignity. To achieve our objective, structural and optical investigations of ZnO annealed at 500°C for 2hrs were carried-out using complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The ZnO nanoparticle crystallite size was determined to be 16.52 nm (see Eqn 13). These findings are in accordance with the report by Noukelag et al 53 . who synthesized ZnO nanoparticles via the green method using extract of Rosmarinus officinalis leaves.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The ZnO nanoparticle crystallite size was determined to be 16.52 nm (see Eqn 13). These findings are in accordance with the report by Noukelag et al 53 . who synthesized ZnO nanoparticles via the green method using extract of Rosmarinus officinalis leaves.…”
Section: Resultssupporting
confidence: 93%
“…The ZnO nanoparticle crystallite size was determined to be 16.52 nm (see Eqn 13). These findings are in accordance with the report by Noukelag et al 53 who synthesized ZnO nanoparticles via the green method using extract of Rosmarinus officinalis leaves. However, their analysis revealed that the ZnO nanoparticles had stronger diffraction and higher crystallinity than the ZnO nanoparticles prepared in the present study.…”
Section: Ftir Spectroscopysupporting
confidence: 93%
“…The calculated band gap of ZnO NPs without calcination and calcinated ZnO NPs was 3.1 and 3.5 eV, respectively, close to pure ZnO (3.3 eV). The material's band-gap depends on factors, such as surface roughness, oxygen vacancy, lattice strain, grain size (Faisal et al, 2021;Noukelag et al, 2020), and calcination temperature. de Almeida et al reported that an increase in band-gap could be due to a rise in the calcination temperature (de Almeida et al, 2021).…”
Section: Band-gapmentioning
confidence: 99%
“…60 % sample has intense orange colour which is quite typical for the natural ZnO mineralzincite [18], but up to our knowledge was never reported for the ZnO films produced by magnetron sputtering. The possibility of observation of zincite phase is also indirectly rejected by the mismatch between reported band gap of zincite which is approximately 3.2 eV [19] and experimentally observed value of 3.08 eV. Also, the presence of zincite phase is not confirmed by XRD (Fig.…”
Section: Resultsmentioning
confidence: 91%